Filsafat Ilmu Sebagai Dasar dan Arah Pengembangan Ilmu Hukum di Indonesia - Mila Karmila Adi (Jurnal Hukum IUS QUIA IUSTUM, 2008)
The development of Legal Science in Indonesia has disappointed the society, since the products of law give no good benefit impact even make more difficulties without any problem solving as the main point of the products. It seems that Legal Science in Indonesia is stuck between Continental and Anglo Legal Systems. Science Philosophy is the right tool to give the basic and direction to the development of legal Science in Indonesia, because the aspects of Science Philosophy, as Knower, Knowing, and Knowledge, will lead the Legal Science in Indonesia developed in the right track. The Legal Science in Indonesia should be based on the religious, humanity, united in diversity, democracy, and social justice, as the basic philosophy of Indonesian nation.